Arsenic Trioxide Cooperate Cryptotanshinone Exerts Antitumor Effect by Medicating Macrophage Polarization through Glycolysis - Tao Jiang; Jian-Bo Huang; Chu-Yu Xu; Yuan-Lin Lv; Jun Lu; Zheng-Qi Zhao; Dan-Qian Yang; Zhao-Huan Lou; Guang-Ji Zhang (Journal of Immunology Research)
Hepatocellular carcinoma (HCC) is an often-fatal malignant tumor with high lethality. Despite advances and significant efficacy in monotherapy, cancer therapy continues to pose several challenges. Novel combination regimens are an emerging strategy for anti-HCC and have demonstrated to be effective. Here, we propose a potential combination for HCC treatment named arsenic trioxide cooperate cryptotanshinone (ACCS). A remarkable synergistic therapeutic effect has been achieved compared with drugs alone in both in vivo and in vitro experiments. Mechanism study indicated that ACCS exerts its therapeutic actions by regulating macrophage-related immunity and glycolysis. ACCS potentiates the polarization of M1 macrophages and elevates the proportion of M1/M2 to remodel tumor immunity. Further molecular mechanism study revealed that ACCS intensifies the glucose utilization and glycolysis in the macrophage by increasing the phosphorylation of AMPK to activating the AMPK singling pathway. In conclusion, ACCS is a highly potential combination regimen for HCC treatment. The therapeutic potential of ACCS as a candidate option for anticancer drugs in restoring the balance of immunity and metabolism deserves further investigation.